Adolescent pregnancy, public policies, and targeted programs in Latin America and the Caribbean: a systematic review - Clara Rodríguez Ribas (Pan American Health Organization, 2021)
Objective. To present and assess evidence from Latin America and the Caribbean (LAC) on public policies and targeted programs which may have influenced variations in adolescent pregnancy or its proximate determinants, and to identify knowledge gaps that require further research. Methods. A systematic review was performed based on the 2015 PRISMA protocol. Five databases were searched for articles published between 2000 and 2019 that refer to at least one country in LAC. The outcomes of interest were adolescent pregnancy or its proximate determinants (sexual behavior, contraceptive use, and/or abortion). Only studies exploring correlations between the outcomes of interest and public policies or targeted programs were included in the analysis. Results. Thirty studies spanning 14 countries were selected for analysis. Twenty-three of these (77%) were not included in prior systematic reviews on adolescent pregnancy. Public policies related to conditional cash transfers and compulsory education have the strongest evidence of correlation with adolescent pregnancy prevention. Emerging research points to the potential positive impact of life-skills programs for adolescents. Evidence from public health policies and programs was limited. Conclusions. Further research which incorporates an intersectional analysis is needed to better understand which policies and programs could lead to steeper declines in adolescent pregnancy in the region. Evidence on effects of expanded family planning services and secondary school attainment upon adolescent pregnancy are particularly absent.